COMPARATIVE STUDY: EFFECT OF PAIN INTENSITY ON BREAST MILK PRODUCTION IN POST SECTIO CAESARIAN MOTHERS WITH ERACS (ENHANCED RECOVERY AFTER CESAREAN SURGERY) AND CONVENTIONAL STUDY METHODS IN THE PUBLIC ROOM UMMI HOSPITAL BOGOR - Syam, Mayrita; Yayat Suryati, Yayat Suryati; Juhaeriah, Juju; Noviyanti, Noviyanti; Murtiningsih, Murtiningsih (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
Delivery by sectio caesarea can cause pain intensity from mild to severe which affects the mobilization of post-op sectio caesarea so that it inhibits early breastfeeding mothers. This study aims to determine the difference in the effect of pain intensity on breast milk production in post-op sectio caesarea mothers with ERACS and conventional methods in the postpartum room at UMMI Hospital Bogor. This study uses a comparative causal design method with a cross sectional approach. Data were taken from the postpartum ward of UMMI Hospital Bogor in May 2022. Respondents from this study were post sectio caesarea mothers with ERACS and conventional methods who met the inclusion criteria. The sampling technique is the Non Probability Sampling technique with the Consecutive Sampling method, with 56 samples consisting of 28 respondents from the ERACS method and 28 respondents from the conventional method. Collecting data using questionnaires and observation sheets. Data analysis used univariate analysis presented in the frequency distribution table, while bivariate data used Independent sample T test and chi-square test. From the results of the study, it was found that the lighter intensity was found in respondents using the ERACS method with a percentage of 32.1% (8 respondents). In the intensity of severe pain there are many respondents with conventional methods with a percentage of 30.4% (17 respondents). Breast milk production in post sectio caesarea mothers with less amount, is mostly found in conventional methods with a percentage of 25% (14 respondents). The amount of milk production that is quite a lot is found in the ERACS method with a percentage of 25% (14 respondents). And based on the independent sample T Test, there was a significant difference in the intensity of post-op sectio caesarea pain in mothers with the ERACS method and the conventional method (p=0.000), and there was also a significant difference in the production of post-op sectio caesarea breast milk in mothers with the ERACS method and the ERACS method. conventional (p=0.000). From the results of the chi-square test, there is a significant effect between the intensity of pain in post sectio caesarea mothers with the ERACS method and breast milk production (p = 0.023), and a significant effect between pain intensity in conventional post sectio mothers and breast milk production (p = 0.000) The conclusion of this study is that there is a difference in the effect of pain intensity on milk production in the ERACS and conventional methods.